Data for "Revisiting the two-dimensional defect-free azimuthal nematic equilibrium on an annulus" - Howell, P (University of Oxford, 2017)
Data for plots in csv format. .csv (“comma-separated values”) is a standard format. In principle the files can be opened in any spreadsheet/data-manipulation package.